Adverse drug events associated with linezolid administration: a real-world pharmacovigilance study from 2004 to 2023 using the FAERS database - Zou, Fan; Cui, Zhiwei; Lou, Siyu; Ou, Yingyong; Zhu, Chengyu; Shu, Chengjie; Chen, Junyou; Zhao, Ruizhen; Wu, Zhu; Wang, Li; Chen, Zhenyong; Chen, Huayu; et al. (Frontiers in Pharmacology, 2024)
Introduction: Linezolid is an oxazolidinone antibiotic that is active against drug-resistant gram-positive bacteria and multidrug-resistant Mycobacterium tuberculosis. Real-world studies on the safety of linezolid in large populations are lacking. This study aimed to determine the adverse events associated with linezolid in real-world settings by analyzing data from the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS). Methods: We retrospectively extracted reports on adverse drug events (ADEs) from the FAERS database from the first quarter of 2004 to that of 2023. By using disproportionality analysis including reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), along with the multi-item gamma Poisson shrinker (MGPS), we evaluated whether there was a significant association between linezolid and ADE. The time to onset of ADE was further analyzed in the general population and within each age, weight, reporting population, and weight subgroups. Results: A total of 11,176 reports of linezolid as the “primary suspected” drug and 263 significant adverse events of linezolid were identified, including some common adverse events such as thrombocytopenia (n=1139, ROR 21.98), anaemia (n=704, ROR 7.39), and unexpected signals that were not listed on the drug label such as rhabdomyolysis (n=90, ROR 4.33), and electrocardiogram QT prolonged (n=73, ROR 4.07). Linezolid-induced adverse reactions involved 27 System Organ Class (SOC). Gender differences existed in ADE signals related to linezolid. The median onset time of all ADEs was 6 days, and most ADEs (n=3778) occurred within the first month of linezolid use but some may continue to occur even after a year of treatment (n=46). Conclusion: This study reports the time to onset of adverse effects in detail at the levels of SOC and specific preferred term (PT). The results of our study provide valuable insights for optimizing the use of linezolid and reducing potential side effects, expected to facilitate the safe use of linezolid in clinical settings. Keywords: Linezolid, adverse drug event, FAERS, disproportionality analysis, pharmacovigilance, real-world analysis.